The Kenyan Experience of Mobile Money and Financial Inclusion - Ramfors,Oscar (2024)
Since Kenya established mobile money in 2007, the amount of usage and diffusion surged. At the same time, financial inclusion has established itself as a topic of great research and importance for policymakers. Kenya is being viewed as one of the top performers on a national level when it comes to mobile money, as M-Pesa was one of the pioneers of introducing MM. As previous literature mainly focuses on national-level data, this thesis uses both national, province, and county-level data to establish how Kenya has developed its MM and FI not only from a national perspective. The main aim is to establish if there are differences in MM diffusion and FI levels between regions within Kenya and what implications this has on these regions. By using a quantitative approach with a multi-level analysis from descriptive statistics, the method allows to establish trends in the data to unveil differences on a regional basis. The main outcome of this thesis is that there are large differences in MM and FI depending on whether you look at national or subnational data. Counties and provinces with higher diffusion of MM also register higher levels of FI. At the same time, these counties also tend to have higher financial health and lower poverty headcount while also accumulating a higher degree of GCP per capita. The Central+Nairobi province has the highest amount of combined MM and FI, and counties in close proximity tend to showcase higher levels of both MM and FI but also GCP per capita. These findings implicate the importance of MM, and could hopefully be useful for policymakers in, but also outside of Kenya in future actions to enhance MM and FI.
Keywords: Mobile Money; M-Pesa; Financial Inclusion; Economic Growth; Kenya; Counties; Provinces; Gross County Product per capita; Gross Provincial Product per capita; Gross Domestic Product per capita; Urbanization; Poverty Headcount; Financial Health